Clinical Thyrotoxicosis Resulting from Liothyronine Augmentation of Antidepressant Therapy in an Adolescent - Benjamin A. Pallant; Claire E. Moore; Lisa Swartz Topor (Case Reports in Psychiatry)
Background/Objective. Thyrotoxicosis, a condition resulting from excessive peripheral thyroid hormone, is typically accompanied by thyroid function tests demonstrating a high free thyroxine (free T4) with appropriate suppression of thyroid-stimulating hormone (TSH). Case report. We describe a 17-year-old female presenting with symptoms of thyrotoxicosis along with suppressed TSH and low free T4, a laboratory pattern concerning for central hypothyroidism. Further history revealed that she was prescribed liothyronine as an adjunct therapy for depression. Discussion. Due to the short half-life of liothyronine, clinical signs and symptoms of thyrotoxicosis may develop before detection by interval lab monitoring. Conclusion. This case highlights the need for close monitoring and caution when treating adolescents with liothyronine and the importance of interpreting atypical laboratory findings within clinical context.